High dimensional model representation (HDMR) and trigonometric transformational HDMR - (:unkn) unknown (WORLD SCIENTIFIC AND ENGINEERING ACAD AND SOC, 2008)
It is well known that mathematical modeling of physical systems is a must in most cases. Amongst many approximation techniques is the High Dimensional Model Representation Method. Here, preliminary analytical attemps are made for a newly developed version of HDMR the Trigonometric Transformational HDMR.
Keywords: multivariate functions; trigonometric functions; High Dimensional Model Representation